Approaches for enhancing productivity of smallholder dairy production in India (Indian Journal of Animal Production and Management, 2024)
Dairy production in India plays an important role in improving the livelihoods of farmers with equity. The milk  production in the country has increased by about 10 times since independence (176.35 million metric tons in  2017-18), and at present accounts for about 67% of total value of output from livestock. The dairy production  systems are complex and generally based on traditional and socio-economic considerations mainly guided  by available feed resources. The traditional feeding system mostly consists of crop by products, natural  grasses supplemented with a little or no concentrates. The seasonal fluctuation in availability of fodder  from natural pasture and scarcity of feed and fodder resources (both quantity and quality) primarily affect  the nutrition in animals, which results in low production and reproductive performance, slow growth rate,  loss of body condition and increased susceptibility to diseases and parasites. Low production potential  of animals, non-availability of critical inputs/services in time, access to capital and markets also hamper  the dairy production. The effective utilization of the available feed and fodder resources and appropriate  supplementation of poor quality crop residue and natural pasture appears to be the necessary steps to  alleviate the nutritional stress of dairy animals. An array of technologies- feed and feeding interventions  have been developed and demonstrated their potential in improving the productivity of dairy animals at  field level with varying success. However, enormous efforts are required to upscale and outscale their  adoption through different extension agencies by educating farmers on efficient management of limited  resources to ensure the long term sustainability and profitability of animal production system. This can  be achieved by the favourable policy and actions in terms of access to micro-credit, assured market and  veterinary services.
Keywords: Dairy production; Participatory research; System approach